2022
DOI: 10.1111/appy.12511
|View full text |Cite
|
Sign up to set email alerts
|

A century of Morita therapy: What has and has not changed

Abstract: We review the history of Morita therapy (MT), which has existed for over 100 years, and examine what has changed over that period and what has not. Classic MT, which was dependent on a highly strict therapeutic approach, gradually lost its pre‐eminence, but at the same time, the fundamental theory of MT was refined. This theory came to be applied to current outpatient MT and adapted to inpatient MT. As MT was refined, a standard training system for therapists was established, adaptations to modern conditions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…Morita therapy, developed by Shoma Morita in 1919, is a Japanese psychotherapy technique that is now used worldwide for nervousness and anxiety disorders [1][2][3][4]. Morita therapy considers fear or anxiety to be a single concept with two facets [1,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Morita therapy, developed by Shoma Morita in 1919, is a Japanese psychotherapy technique that is now used worldwide for nervousness and anxiety disorders [1][2][3][4]. Morita therapy considers fear or anxiety to be a single concept with two facets [1,4].…”
Section: Introductionmentioning
confidence: 99%
“…Morita therapy, developed by Shoma Morita in 1919, is a Japanese psychotherapy technique that is now used worldwide for nervousness and anxiety disorders [1][2][3][4]. Morita therapy considers fear or anxiety to be a single concept with two facets [1,4]. One aspect represents the fear we broadly recognize as being frightened, whereas the other aspect indicates the positive side of fear, that is, the desire to live.…”
Section: Introductionmentioning
confidence: 99%
“…Morita Therapy (MT) is an original psychotherapy developed by Japanese psychiatrist Shoma Morita in 1919 [ 1 ], which has been re-evaluated and has attracted much attention internationally to date [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Morita therapists help patients move away from preoccupation and struggle, which have been implied in interfering with the natural recovery process. [23] Previous publications [24,25] have elaborated the uniqueness and commonalities of NT and MT, proposed the theoretical basis underlying the combination of these two therapies, and further applied them in the clinical observation. The results showed that NT first evoked the patients' positive emotions, and MT then improved behavioral initiative.…”
Section: Introductionmentioning
confidence: 99%
“…The main purpose of MT is to help patients accept the view that unpleasant symptoms are the normal part of human emotions rather than negative things to be eliminated. Morita therapists help patients move away from preoccupation and struggle, which have been implied in interfering with the natural recovery process [23] . Previous publications [24,25] have elaborated the uniqueness and commonalities of NT and MT, proposed the theoretical basis underlying the combination of these two therapies, and further applied them in the clinical observation.…”
Section: Introductionmentioning
confidence: 99%